Beneficiation Studies of Bajaur Manganese Ore by Different Processing Techniques: Benefication of Manganese Ore - Khan, Farid Ullah; Riaz, Muhammad; Yamin, Asma; Bilquees, Rubina; Muhammad, Nisar (Biological Sciences - PJSIR, 2010)
The manganese ore of Bajaur Agency of Pakistan was subjected to flotation, heavy medium separation, gravity concentration and magnetic separation techniques for beneficiation. The original composition of the manganese ore was 45.56% Mn , 4% Fe O , 40% SiO The Mn content was raised to a maximum ~ 48.76 % in the concentrate with the recovery of ~ 67.78 % through flotation technique. Other techniques rendered marginal increase in Mn concentration against the theoretical possibility of substantial enrichment by rejecting the ~ 20 % gangue minerals. The separation of manganese minerals from associated gangue was difficult, due to mineralogical complexity of the ore, extreme fineness of the particle size, texture and minerals intergrowth. High Mn/Fe ratio, phosphorus, and silica contents were within tolerable limits for utilisation of the ore in ferro-manganese production.